Plaque angiogenesis and intraplaque hemorrhage in atherosclerosis - Parma, Laura; Baganha, Fabiana; Quax, Paul H.A.; de Vries, Margreet R. (European journal of pharmacology, 2017)
Acute cardiovascular events, due to rupture or erosion of an atherosclerotic plaque, represent the major cause of morbidity and mortality in patients. Growing evidence suggests that plaque neovascularization is an important contributor to plaque growth and instability. The vessels’ immaturity, with profound structural and functional abnormalities, leads to recurrent intraplaque hemorrhage. This review discusses new insights of atherosclerotic neovascularization, including the effects of leaky neovessels on intraplaque hemorrhage, both in experimental models and humans. Furthermore, modalities for in vivo imaging and therapeutic interventions to target plaque angiogenesis will be discussed.